Modern Woodcut ART in Vietnam in the Early 21st Century (London Journal of Research In Humanities and Social Sciences, 2024)
Modern woodcut art in Vietnam has a long-standing tradition from various folk woodcut art styles, such as Dong Ho, Hang Trong, Lang Sinh, Do The, and Kim Hoang. In 1925, the establishment of the Dong Duong School of Fine Arts marked an important milestone in the development of modern woodcut art. Today, artists are experimenting with various creative trends, innovating techniques in woodcutting, printing, reduction woodcuts, and notably, some have harnessed the power of Industry 4.0 to create contemporary and high-quality artistic works. During this period, modern woodcut art exhibits newfound vitality, diversity in artistic techniques, various creative trends, rich subject matter, diverse material techniques, and expressive forms reflecting the region's culture, which is the hallmark of modern woodcut art in Vietnam. In general, every artist using their individual strengths in practical creativity has palayed a part in changing the face of modern Vietnamese art in the early 21st century.
Keywords: teaching practices; school volleyball; verbal intervention; didactic regulation; acceptance and inclusion of refugee students; acceptance and respect for otherness; cooperation; empathy and emotional intelligence; experiential learning; open school; reduction in intra-school violence; strengthening of family ties.; Convergence; social capital; NREGA/MGNREGA/MGNREGS; BPL and APL Household; diversity; Vietnam.; folk woodcut art; modern woodcut art; 21st-century; creative work